2014
DOI: 10.1097/prs.0000000000000525
|View full text |Cite
|
Sign up to set email alerts
|

Observed Changes in the Morphology and Phenotype of Breast Cancer Cells in Direct Co-Culture with Adipose-Derived Stem Cells

Abstract: Direct intercellular contact between carcinoma cells and adipose-derived stem cells by means of exosomal vesicular exchange was revealed. Breast cancer cells displayed a change towards a more malignant phenotype associated with higher rates of metastasis and worsened prognosis. As cell-assisted lipotransfer is often performed after breast cancer surgery, transfer of adipose-derived stem cells might lead to deterioration of prognosis in case of recurrence as it has been described for inflammatory breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 38 publications
(29 reference statements)
1
29
0
Order By: Relevance
“…In a co-culture of breast cancer T47D cells and adipose stem cells, Kuhbier et al noted that T47D cells changed in morphology and phenotype after 14 days [27] . Moreover, it was found that cellular activity of T47D was also significantly increased.…”
Section: Laboratory Studies Of Adsc and Breast Cancermentioning
confidence: 99%
“…In a co-culture of breast cancer T47D cells and adipose stem cells, Kuhbier et al noted that T47D cells changed in morphology and phenotype after 14 days [27] . Moreover, it was found that cellular activity of T47D was also significantly increased.…”
Section: Laboratory Studies Of Adsc and Breast Cancermentioning
confidence: 99%
“…Thereby it was shown that the expression level of transcriptional genes for typical malignant markers is significant higher in the direct co-culture than in the single culture [4]. This suggests that adipose-derived stem cells could have the potential to promote the tumor growth of breast cancer cells and therefore that it could pose an oncological risk [4]. one part of the removed fat tissue is fermented and centrifuged to gain the stromal vascular fraction containing the adipose-derived stem cells [4].…”
Section: Introductionmentioning
confidence: 99%
“…Even though the clinical evidence concerning safety and efficiency are not clear, the clinical application of this stem cell therapy is on the increase [3]. In the last few years, adipose-derived stem cells were associated with the recurrence of cancerous breast tumors in in vitro studies so that adipose-derived stem cells could be discussed as the cause of certain tumors in current studies [4][5][6]. In this context, the influence of adipose-derived stem cells on the gene expression of breast cancer cells with direct cell contact was investigated [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations